Maximizing Speculative Urban Development: An Empirical Analysis of Local Governance in Milwaukee - Gieryn, Nathaniel (My University, 2002)
After being awarded major league baseball's all-star game, the city of Milwaukee felt that the time was right to build a new stadium to take full advantage of this prestigious opportunity to showcase both their team and the city. The parties involved settled on a $250 million retractable-roof facility as the ideal stadium for the future, a stadium that would be one of the finest in baseball. In the spring of 1996, the city of Milwaukee attempted to influence negotiations by offering to contribute $100 million towards construction costs if the stadium was built in the downtown area. This was no surprise as the city had already invested over one billion dollars downtown to pursue a multitude of flagship projects including the Riverwalk, Grand Avenue Mall, and the Calvatrava addition to the art museum to inspire development in the region. This was characteristic of cities in the early 1990s, when Milwaukee and most other North American cities were pursuing massive speculative developments with hopes that their investment would help to reinvent the region and inspire economic growth. These developments provided evidence for a reorientation of local policy that was identified as the emergence of 'entrepreneurial governance'. In this sense, the downtown proposal for the baseball stadium was the next flagship project for the city of Milwaukee to pursue with hopes of inspiring growth in the region and recouping their investment.
Figures; Maps; Bibliography
Keywords: Urban Development; Milwaukee